Alignment of Human Competencies with Mobile Phone Technology and Business Strategies by Women‐LED SMEs in South Africa. Issue 1 (5th December 2017) - Ajumobi, Deborah O.; Kyobe, Michael
Abstract: Women‐led SMEs are faced with challenges that inhibit the performance of their businesses. By aligning their human competencies, mobile phone technology and the appropriate business strategy, they can steer their businesses to better performance. However, there is a scarcity of studies providing insight into how they can achieve this. Given the existence of the interplay between human competencies, mobile technology and business strategy, the perspective of alignment as Gestalts was adopted to determine the best way women‐led SMEs may align these three aspects. Data was collected from 70 women‐led SMEs in four provinces in South Africa and analysed using cluster analysis. Of the four clusters that emerged, one performed highly. This study contributes to theory by showing the value of Gestalts theory in assessing the configuration and patterns of organisational variables; and to practice, by providing insight into ways women‐led SMEs can combine these three variables to achieve high business performance.